Pendampingan Pengisian SPT Tahunan Melalui E-Filling Bagi UMKM Anggota “ACSB” Surakarta - Suhardi, Edi; Fatonah, Siti; Susila, Linda Nur; Susanti, Nani Irma; Haryanto , Aris Tri; Mirnayani, Mirnayani (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The purpose of community assistance activities is to provide socialization and assistance in filling the Annual Tax Return through E-Filling for 25 UMKM Members of ACSB Surakarta.  The activity was carried out on Tuesday, March 27, 2024 at the ACSB Surakarta office using the Participatory Learning and Action (PLA) method. Socialization and assistance on taxation provisions for MSMEs, procedures for submitting e-fin application forms, registering e-filling accounts and activating e-filling accounts to create e-filling accounts in organizing SPT 1770, SPT 1770s and SPT 1770ss and implementing online SPT filling in e-filling, so that MSMEs members of ACSB Surakarta can report their SPT. The results of mentoring activities participants can understand tax obligations, fill in the Annual Tax Return correctly, avoid delays in tax payments, and increase awareness about the importance of taxes.